Educação Corporal: uma análise comparada entre a Colômbia e a Argentina - Almeida, Felipe Quintão de (2018)
This paper describes two critical perspectives on the Physical Education tradition in South America. Both perspectives, although located in different countries (Colombia and Argentina), use the same expression: Body Education. In methodological terms, literature review was conducted on the works by two representative authors of the aforementioned theoretical frameworks: Luz Elena Gallo and Ricardo Crisorio. After describing these perspectives, this paper highlights the similarities and differences between the proposals under analysis and outlines some problematizations regarding both perspectives.